Contrastive phraseology languages and cultures in comparison - Cotta Ramusino, Paola; Mollica, Fabio, 1976- (Cambridge Scholars Publisher, 2020)
This volume is addressed to researchers in the field of phraseology, and to teachers, translators and lexicographers. It is a collection of essays offering a comprehensive, modern analysis of phrasemes, embracing a wide range of subjects and themes, from linguistic, both applied and theoretical, to cultural aspects. The contrastive approach underlying this variety of themes allows the divergences and analogies between phraseological units in two or more languages to be outlined.